2019
DOI: 10.5114/wiitm.2019.86773
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to improve long-term results of laparoscopic adjustable gastric banding with appropriate patient selection?

Abstract: Introduction: The gastric band is still offered as a good bariatric option for highly motivated and carefully selected patients. The question is whether this faith is justified or not. Aim: To assess long-term clinical outcomes of patients who underwent laparoscopic adjustable gastric banding (LAGB) at a single bariatric center and to examine variables associated with patients' adherence to scheduled postoperative appointments. Material and methods: A retrospective review of patients who underwent LAGB between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Similar results were obtained by other authors, who showed that the 5-year mean percentage of excess weight loss during the observation period was 34% [24]. However, a recent analysis showed that this effect was not permanent with long-term observation over 7.5 years [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were obtained by other authors, who showed that the 5-year mean percentage of excess weight loss during the observation period was 34% [24]. However, a recent analysis showed that this effect was not permanent with long-term observation over 7.5 years [25].…”
Section: Discussionsupporting
confidence: 90%
“…Recent meta-analyses showed that short-and mediumterm weight loss outcomes after LAGB were poor compared with other bariatric procedures, but the number of RCT studies for the comparison in these analyses was low: only 2 RCT studies compared RYGB vs LAGB, and 1 RCT compared LAGB vs SG [18,26]. The mean 1-year %EWL for RYGB, SG, and LAGB was 67.3%, 71.2%, and 40.6%, respectively [25]. Other authors presented a case series analysis of long-term outcomes among 208 patients with LAGB [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors identified as positive prognostic factors for postoperative weight loss, the attendance of a high number of outpatients visits and the patients’ compliance [ 47 , 48 ]. Orlowski et al, investigated this issue in a recent review, concluding that compliance was an independent prognostic factor for weight loss after LAGB in long-term observation and older age was the only factor associated with better compliance [ 49 ]. Conversely, opposite results were reached by Leca et al on 99 LAGBs.…”
Section: Discussionmentioning
confidence: 99%
“…The device has experienced a decline in popularity as a primary bariatric surgical option due to high rates of late complications and device failure, as documented in several studies. [1][2][3][4] Understanding these potential complications is crucial when evaluating the safety of abdominal contouring procedures in Lap-Band patients, as the presence of the device can potentially impact surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%